The benefits of research-embedded training camps in sport sciences - Girard, O.; Brocherie, F. (International Journal of Sports Physiology and Performance, 2025)
Background: Sport scientists aim to enhance athletic performance by developing, implementing, and evaluating evidence-based strategies. However, a common challenge to maximize sport science`s impact is the limited involvement of "research end users" (ie, athletes, coaches, and practitioners) in contextualizing these strategies. To address this, research-embedded training camps (RETCs) offer a collaborative opportunity bringing together all stakeholders to tackle real-world challenges by blending scientific insight with practical application for better knowledge translation or production.